Analysis of the Iranian Government\'s Economic Authorizations in Response to the COVID-19 Crisis - Younes Nobakht (مجله علم‌سنجی کاسپین, 2022)
Background and aim: The coronavirus disease (COVID-19) pandemic not only triggered a wave of infections and deaths, but also plunged various countries into a particular economic crisis. The aim of this study was to analyze the Iranian government's economic authorizations in response to this crisis. Materials and methods: This applied descriptive-analytical study was performed using content analysis. The statistical population was all authorizations issued by the National Centre for COVID-19 Control during February 2020-March 2022. The required data and information were extracted and used with reference to the information base for monitoring the economic impact of COVID-19. Findings: The results indicated that of the 573 authorizations issued during this period, 47 were attributable to the state economy, with the issuance of 19 authorizations to businesses leading the state economy. Further, the amount of economic support provided by the government in the various economic sectors showed that the government provided the most economic support from the same sector, 750,000 billion Rials to the business sector. Moreover, the study of the government's approach to economic policy suggested that the predominant approach was the use of fiscal policy instruments, which were used more, at 67%, than monetary policy instruments, at 33%. Conclusion: The results have demonstrated that while the government has attempted to minimize the economic problems caused by the COVID-19 pandemic through prompt, timely, and appropriate authorizations, it must be remembered that in addition to the negative economic impact of the COVID-19 pandemic, the Iranian government must also counter economic sanctions imposed by the United States.